Avaliação da qualidade da atenção básica em 37 municípios do centro-oeste paulista: características da organização da assistência - Castanheira, Elen Rose Lodeiro [UNESP]; Dalben, Ivete [UNESP]; Almeida, Margareth Aparecida Santini de [UNESP]; Puttini, Rodolfo Franco [UNESP]; Patricio, Karina Pavão [UNESP]; Machado, Dinair Ferreira [UNESP]; Caldas Júnior, Antônio Luiz [UNESP]; Nemes, Maria Inês Battistella (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 2009)
No Estado de São Paulo, existe uma rede extensiva de serviços de Atenção Básica (AB) com perfil organizacional heterogêneo e pouco conhecido. Este estudo objetiva caracterizar a organização dos serviços de AB em 37 municípios do Centro-oeste paulista, como primeira etapa de um projeto de avaliação da qualidade desses serviços. Trata-se de um estudo transversal conduzido mediante questionário estruturado, autorrespondido pelos gerentes e equipes locais, com questões que abordam características institucionais e de organização e gerência do trabalho. Esses questionários foram enviados para 131 UBS, distribuídas em 37 municípios. Obteve-se resposta de 113 unidades (87%) localizadas em 32 municípios (86,4%). do total de unidades, 57 (50%) são UBS tradicionais, 26 (22,8%), Unidades de Saúde da Família, e 31, (27,2%) organizadas segundo formas mistas. A maioria dos serviços (62%, 70/113) não trabalha com área de abrangência delimitada de modo planejado. Os serviços se polarizam entre aqueles que realizam entre 70 e 100% de consultas médicas agendadas (37,6%, 41/109), e aqueles que realizam entre 70 e 100% de não agendadas (39,4%, 43/109). Não possuem conselhos locais organizados 65 unidades (63,7%, 65/102). Os dados coletados permitem discutir as características dos principais programas, procedimentos e ações realizados pelos serviços. Os perfis organizacionais predominantes apontam a presença de deficiências de estrutura e processo em relação às diretrizes do SUS. O desenvolvimento de instrumentos de autoavaliação permite que as equipes se apropriem, de forma crítica, de seu trabalho, e possam elaborar novos arranjos tecnológicos para melhoria da qualidade.

The State of São Paulo, Brazil, has a broad network of primary health care services (PHCS) whose organizational profile is heterogeneous and not well known. This study analyzes the organization of PHCS in 37 municipalities located in the central-west region of São Paulo, as the first part of a broader project that evaluates the quality of these services. This is a cross-sectional study conducted through a structured questionnaire answered by the local managers and health teams. The questions addressed institutional characteristics and the organization and management of the work process. The questionnaires were sent to 131 UBS (Primary Health Care Units) distributed across 37 municipalities. There were responses from 113 units (87%) located in 32 municipalities (86.4%). of the overall number of units, 57 (50%) are traditional UBS, 26 (22.8%) are family health units, and 31 (27.2%) are mixed. Most services (62%, 70/113) do not work with catchment areas delimited in a planned way. Services are divided between those who perform 70% to 100% of scheduled medical consultations (37.6%, 41/109) and those who perform 70% to 100% of non-scheduled consultations (39.4%, 43/109). Sixty-five units (63.7%, 65/102) do not have community-based committees. Based on the collected data, it is possible to discuss the main features of the health programs, procedures and activities carried out by PHCS. The predominant organizational profiles reveal deficiencies of structure and process in relation to the guidelines issued by SUS (Brazil's National Health System). The development of self-assessment instruments allows the teams to appropriate their work in a critical way and to carry out new technological arrangements to improve the quality of the care provided.
Evaluation of the quality of primary care health services in 37 municipalities in the State of São Paulo, Brazil: organizational dimensions of care
Keywords: Atenção primária; Avaliação; Qualidade de serviços de saúde; Primary Care; Assessment; Quality of Health Services